Automated imaging technologies for the diagnosis of glaucoma : a comparative diagnostic study for the evaluation of the diagnostic accuracy, performance as triage tests and cost-effectiveness (GATE study) /: a comparative diagnostic study for the evaluation of the diagnostic accuracy, performance as triage tests and cost-effectiveness (GATE study). (January 2016) - Azuara-Blanco, Augusto
No abstract available